2019
DOI: 10.3390/molecules24213815
|View full text |Cite
|
Sign up to set email alerts
|

Nature-Inspired Polymerization of Quercetin to Produce Antioxidant Nanoparticles with Controlled Size and Skin Tone-Matching Colors

Abstract: Plant polyphenols have received considerable attention in recent years due to their ability to undergo oxidation-triggered self-polymerization, forming biocompatible versatile coatings and templated nanoparticles (NPs) that can be leveraged for a variety of biomedical applications. Here we show for the first time that untemplated NPs can be conveniently synthesized from the abundant plant polyphenol quercetin (QCT) simply by incubation with an oxidizing agent in a universal organic solvent, followed by self-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…Cells were obtained from the American Type Culture Collection (ATCC, Manassas, VA, USA) and cultured as described in an earlier publication. 26 For the experiment, cells were seeded in 96well plates at 1.0 × 10 4 cells per well (n = 4) and allowed to adhere for 24 h. The next day, the cells were treated with 0−1000 μg mL −1 of PDA NPs in complete media for 24 h. At the end of the incubation period, the MTT assay was carried out as previously described. 26 Cell viability was expressed as % viability relative to cells treated with complete media only.…”
Section: % Accumulationmentioning
confidence: 99%
“…Cells were obtained from the American Type Culture Collection (ATCC, Manassas, VA, USA) and cultured as described in an earlier publication. 26 For the experiment, cells were seeded in 96well plates at 1.0 × 10 4 cells per well (n = 4) and allowed to adhere for 24 h. The next day, the cells were treated with 0−1000 μg mL −1 of PDA NPs in complete media for 24 h. At the end of the incubation period, the MTT assay was carried out as previously described. 26 Cell viability was expressed as % viability relative to cells treated with complete media only.…”
Section: % Accumulationmentioning
confidence: 99%
“…Consequently, absorbance peaks were observed at 256, 290, and 340 nm. It has been shown that quercetin can be deprotonated by the specific oxidation of the -OH groups at the catechol site with a shift base agent (sodium methoxide) in the presence of free -OH groups at C 3 on ring C and at C 7 on ring A, which are known to be responsible for electronic absorption peaks recorded at 348 nm (band I) and 300 nm (band II), respectively [ 32 , 52 , 53 ]. As mentioned above, an absorption peak of 256 nm represents the free -OH group at C 5 on ring A.…”
Section: Resultsmentioning
confidence: 99%
“…To identify the interaction between the deprotonated quercetin and IronQ, the FTIR spectra, and characteristic bands of pure quercetin, the deprotonated quercetin and IronQ were compared, as shown in Figure 3 and Table 1 [ 60 – 62 ]. We observed that the aryl ketonic stretching C 4 =O at 1664 cm −1 of quercetin disappeared, while new strong C=C stretching bands at 1592 cm −1 and 1569 cm −1 appeared for deprotonated quercetin and IronQ, respectively [ 52 , 53 ]. The results suggest that as the deprotonation of C 3 -OH occurred, an intrastructure rearrangement resulted in, at least, two resonance aryl ketones (OC 3 =C 4 O − ) in their molecules being affected by the loss of the C 4 =O stretching signal.…”
Section: Resultsmentioning
confidence: 99%
“…The method was adapted from the Folin-Ciocalteu total phenol assay. 23,24 Briey, the Folin-Ciocalteu reagent was diluted 1 : 10 in ultrapure water. Gallic acid standards were prepared in the range 12.5-200.0 mg mL À1 in ultrapure water, and 125 mL of each dilution were placed in a separate well of an untreated 24-well plate.…”
Section: Total Phenol Content Of Polyphenol-coated Platesmentioning
confidence: 99%